WAYS OF CONVEYING THE MEANING OF CULTURALLY MARKED VOCABULARY IN THE ENGLISH TRANSLATION OF "A TALE OF THE BLISS BIRD" BY VSEVOLOD NESTAIKO - ZOSIMOVA, Oksana (Linguistic and Conceptual Worldviews, 2023)
Despite the fact that the problem of conveying the meaning of culturally marked vocabulary has always received a lot of critical attention from the scholars, rendering of Ukrainian fairy tales realia into other languages remains a topical issue because of the growing interest in our culture nowadays and the need for adequate translation in the field of various genres of fiction. In this context special attention must be paid to the process of translating literary fairy tales that also include a lot of culturespecific elements but have not been studied from this perspective yet. The purpose of this research is to identify the ways of conveying the meaning of culturally marked vocabulary in the English translation of Vsevolod Nestaiko’s "A Tale of the Bliss Bird". The main tasks of the study are as follows: to outline the strategies, methods, and techniques of rendering the meanings of ethno-marked components of the text into English, to find out what factors determined the choice of particular methods by the translator and how justified the corresponding text transformations are. The methods and techniques used in this research include a total sampling technique (to select the research data) and basic methods of linguistic and translation analysis, namely: analytical, descriptive, and comparative methods - for analyzing and comparing different linguistic realia in the original and their equivalents in the translation, to identify and describe the ways of rendering Ukrainian realia into English. It has been found that the translator of the text, Vasyl Baryshev, mainly employed adaptation and simplification strategies, which in most cases is justified by the age of the target audience of the fairy tale, the inappropriateness of overloading the text with transcribed foreign language realia with explanations that could interfere with children’s perception and lead to the loss of dynamism of the plot. Some of the author’s occasionalisms (nonce words), carrying vivid national and cultural connotations, are technically impossible to be conveyed by means of the English language. So, the translator had to employ the techniques of omission or substitution, use functional analogues and contextual equivalents. In the process of translating onyms, in particular the names of the main characters, V. Baryshev quite successfully applied a creative approach (though with certain inaccuracies), forming in the English version of the text a coherent anthroponymic microsystem that meets the demands of the fairy tale genre.